Anthocyanin extraction from plant tissues: A review. Issue 14 (22nd September 2017) - Silva, S.; Costa, E. M.; Calhau, C.; Morais, R. M.; Pintado, M. E.
ABSTRACT: Anthocyanins have gathered the attention of the scientific community mostly due to their vast range of possible applications. They have been the center point of the research in many different fields, among which is food development, where their innate coloring, antioxidant capacity, and biological potential open interesting venues to the development of new food additives and functional foodstuffs. As the range of application grows, so does the necessity to obtain these compounds, and since they are naturally occurring, the most common way to obtain anthocyanins is to extract them from different plant sources, such as fruits and flowers. Several efforts have been made to develop methods that allow for better extraction yields and higher purification rates therefore this review aims to compile the information regarding extraction and purification procedures in a comprehensive manner.